LONELINESS SMARTPHONE USERS IN TERM OF GENDER DIFFERENCES IN CLASS XI STUDENTS OF SMA N 9 SEMARANG - Yuli Triwidodo; Endah Kumala Dewi (Jurnal EMPATI, 2012)
Lonely teenager who access the smartphone is an individual's attempt to cope with their anxiety by accessing the Internet, especially social media to connect with others who are far away through smarphone that individuals have the result they ignore direct communication or face-to-face with people who are near the individual. It could be said that they are not lonely online but offline they feel lonely.This study aims to describe differences lonely teenager who access social media via smartphones. In addition, this study also aims to determine the differences lonely teenager who access social media via smartphones views of gender on students' high school N 9 Semarang. The study sample used by researchers is a class XI student of Semarang SMA N 9, 150 samples consisting of 75 boys and 75 girlsTesting this hypothesis using the Mann-Whitney test. The results of testing the validity of the items in this study moves from 0.302 to 0.792 with a reliability of 0.964. Based on the data analysis using the Mann-Whitney test. The results of hypothesis testing produces a significance value of 0.550 (p> 0.05). Based on these results we can conclude that there is no difference lonely teenager who access social media via smartphones in terms of gender.